Species of the genus Euseius Wainstein (Acari: Phytoseiidae: Amblyseiinae) from Taiwan - Liao, Jhih-Rong; Ho, Chyi-Chen; Ko, Chiun-Cheng (Zootaxa, 2017)
The six mite species of the genus Euseius Wainstein from Taiwan are reviewed, including E. ovalis (Evans), E. daluensis sp. nov., E. macaranga sp. nov., E. paraovalis sp. nov., and two species recorded for the first time in Taiwan, E. aizawai (Ehara & Bhandhufalck) and E. circellatus (Wu & Li). Measurements of these species and an identification key for adult females of the six Euseius species from Taiwan are provided.